Methods for Increasing Power Efficiency of Heating Furnaces Applied in Metallurgical and Mechanical Engineering Industries - M. L. German; S. M. Kabishov; A. A. Oznobishin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper analyzes experimental data and results of balance tests of two continuous heating furnaces applied in mechanical engineering and metallurgical industries. Furnace power technological characteristics  and dependences of these characteristics on equipment productivity have been determined in the paper. The analysis has made it possible to reveal reasons of higher efficiency of a heating furnace used at BSW Rolling Mill-320 and formulate recommendations on reduction of fuel consumption in operating and designed combustion furnaces applied in mechanical engineering and metallurgical industries.